The effect of Palliative Care to Quality of Life of People who Living with End Stage Renal Disease in Community - อาจสันเที๊ยะ, จินตนา; ติลภัทร, จุฑามาศ (Journal of The Royal Thai Army Nurses, 2019)
This research was quasi experimental study. The purposes were to study the result of palliative care to quality of life of people who living with end stage renal disease in community. The samples were selected by purposive sample with inclusion criteria. 35 end stage renal disease patients in 1 group pretest and posttest in palliative care. The instruments were composed of 1) General information and symptom 2) QoL questionnaire of Ferrans and Powers Dialysis version-III with content validity = 0.65, reliability with Cronbach’s alpha coefficient = 0.843. 3) Evaluation form of palliative care 4) Meditation healing exercise of SKT. The steps in palliative care composed of following 1) making relationship, 2) making understanding 3) making mindfulness 4) making acceptance and bereavement care. Descriptive statistics analysis and inferential statistics analysis for hypothesis testing by using readiness program. Pairt-Test in pretest and posttest of quality of life in palliative care. The result found that 71.4% was woman, 57.14% was the average age at 70 years old, 77.1% was primary level of education, 57.1% of patients had social welfare with gold card care. The symptom of the end stage renal disease patient before and after found that itching had significant difference (p-value at .048). Comparison before and after palliative care had quality of life in health & functioning, psychological & spiritual, and family significant difference (p value <.05). There was no significant difference of Social & Economic quality of life. Conclusion, palliative care for people who living with end stage renal disease in community composed of the steps of making Relationship, Understanding, Mindfulness, Acceptance that were supported in working within understanding the context of community and led to develop quality of life in their envelopment.